Deploying Mobile Trend in Higher Education Institutions in Malaysia - Idris, M.; H Hussain, A. (International Journal of Engineering and Technology, 2019)
The revolution of mobile technology has been spreading gradually around the world. Mobile technologies are a bridge between online social connections and real-world social interaction. This paper will discuss the results from an exploratory study on measuring the challenges of adopting mobile technology in Malaysian Higher Education Institutions (HEIs). For this purpose, an online 15-item questionnaire was distributed among academicians from public and private universities in Malaysia from which 42 respondents were recruited as sample. Preliminary results suggest that people, policies and technologies are a good construct for measuring the challenges of adopting mobile technology for a â€œmobile trendâ€ in Malaysian HEIs. The present study confirms previous findings and contributes additional evidence on issues and challenges in implementing mobile learning and proposes that further studies taking these variables into account be undertaken.Â Â Â